Punitivism with a human face: criminal justice reformers' international and regional strategies and penal-state making in Argentina, Chile and beyond = Punitivität mit einem menschlichen Anstrich : die internationalen und regionalen Strategien von Rechtsreformern und die Verbreitung des strafenden Staates in Argentinien, Chile und anderswo - Hathazy, Paul (Kriminologisches Journal, 2016)
In this paper I study the regional import-export strategies of Latin American criminal justice reformers and the emergence of a regional hub of reform expertise. Analyzing these regional processes - sidelined by most studies, focusing on central-country to periphery-country north-south circulations - I account for the contents and implementation-designs of the criminal procedure reforms in the last two decades in many Latin American states, increasing their punitive capacities and legitimacy. I dissect the Argentine and Chilean reform processes in the 1980s and 1990s, situated at the core of these regional dynamics. Locating these regional processes within historical transatlantic and continental circuits of penal expertise I show that these strategies and institutions result from struggles within national criminal justice fields and from reformers exporting their fights regionally to regain power at home or to dispute it to core-countries´ agents.